How satisfied are inbound medical tourists in Malaysia? a study on private hospitals in Kuala Lumpur - Musa, Ghazali; Doshi, R.R.; Wong, K.M.; Thirumoorthy, T. (Taylor & Francis, 2012)

(untitled)
The study explores inbound medical tourists’ satisfaction from 137 respondents sampled using the combination of purposeful and convenience samplings in five private hospitals in Kuala Lumpur. In descending order of scores, medical tourists are most satisfied with doctors, nurses, hospital services, hospital atmosphere, and hospital facilities. Hospital facilities and doctors are the two most important dimensions in influencing the overall satisfaction. There are significant differences in the levels of satisfaction within demographic profiles. The article contributes to knowledge on the establishment of dimensions and items pertinent to measuring medical tourists’ satisfaction and the results provide insights into managerial and marketing implications.